Pengaruh Modal Manusia terhadap Transisi Tenaga Kerja Formal Menjadi Informal pada Masa Pandemi Covid-19 - Tasmilah, Tasmilah; Pratomo, Devanto Shasta; Syafitri, Wildan (UI Scholars Hub, 2023)
This study aims to examine the effect of human capital on the transition of formal to informal labor during the Covid-19 pandemic. Human Capital in this study includes education, training, experience, skills, and the use of digital technology and the internet. Using Sakernas data in August 2019 and 2020, logistic regression was conducted to estimate the effect of human capital on the formal labor transition. Based on analysis, human capital has a significant effect on the transition of formal labor during the pandemic. Education, training, and use of digital technology and the internet will prevent the transition of formal to informal labor. Meanwhile, experience and training have a positive effect on the transition of formal to informal labor.